2010
DOI: 10.1111/j.1365-2699.2009.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Tropical dry forest trees and the relationship between local abundance and geographic range

Abstract: Aim  To test the macroecological principle that a positive relationship exists between local abundance and geographic range size for tree communities in the tropical dry forest. Location  Two tropical dry forest (TDF) regions on the Pacific coast of Mexico: one near Chamela, Jalisco; the other near Huatulco, Oaxaca. Methods  We recorded species presence and relative abundance of trees and lianas from over 40 locales in each of the study regions using transects across an elevational gradient. We then compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
2
11
0
5
Order By: Relevance
“…We see no reasons to expect this bias: three plots we studied are in subtropical lowland forest, and their environmental conditions are similar to the entire subtropical area. Our results are consistent with the few studies on tree species we found: some reported no correlation between local abundance and range size [25], and others found either positive or negative, though weak relationships [50], [59].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We see no reasons to expect this bias: three plots we studied are in subtropical lowland forest, and their environmental conditions are similar to the entire subtropical area. Our results are consistent with the few studies on tree species we found: some reported no correlation between local abundance and range size [25], and others found either positive or negative, though weak relationships [50], [59].…”
Section: Discussionsupporting
confidence: 93%
“…There was no relation, consistent with the result from Williams et al . [25]. Evidently other factors accounting for species differences in abundance are much more important than the location of a range center.…”
Section: Discussionmentioning
confidence: 99%
“…These endemics are often numerically dominant compared to most co-occurring pandemics [19,20], further suggesting that the lack of a positive abundance-range size relationship is a general phenomenon on coral reefs. Similarly, on land, some endemic species can be locally abundant [21], contributing in some cases to significant negative interspecific relationships between abundance and distribution [17].…”
Section: Resultsmentioning
confidence: 99%
“…No -the authors classified species distributions into three categories (endemic, Mediterranean, widely distributed) Pither (2003) Tolerance Yes -the author measured area occupancy of species endemic to continental United States of America and Canada Williams et al (2010) Tolerance No -the authors excluded occurrence records outside the Western Hemisphere…”
Section: Studymentioning
confidence: 99%